The Energy in the Arctic - Hoogensen Gjørv, Gunhild (University of Washington, 2016)
Source at https://jsis.washington.edu/arctic/wp-content/uploads/sites/21/2016/05/AIRS-Issue-4.pdf . Introduction : The inaugural Fulbright Arctic Initiative (FAI) program is moving into its final phases, and FAI scholars are looking towards finding new and continued synergies between their research efforts. The articles in this issue of the Arctic and International Relations Series represent the excellent work done by scholars contributing to the theme of “energy” for the FAI project. This collection exemplifies not only the FAI team’s diverse approaches to energy but also the Arctic researchers’ energy and dedication to scholarship itself. This volume presents the independent, individual projects by some of the FAI scholars. Though each author addresses the issue of energy from a different perspective, their combined efforts tell a comprehensive story about energy in the Arctic and the ways in which energy issues will likely develop in the future.